2021
DOI: 10.1021/acs.energyfuels.1c00232
|View full text |Cite
|
Sign up to set email alerts
|

Zero Flowback Rate of Hydraulic Fracturing Fluid in Shale Gas Reservoirs: Concept, Feasibility, and Significance

Abstract: A high flowback rate of hydraulic fracturing fluid (HFF) yields a high gas production rate in a tight sand gas reservoir. This idea is well followed when it comes to the hydraulic fracturing of a shale gas well. Therefore, numerous studies have focused on increasing the flowback rate of HFF in shale gas reservoirs to mitigate the water blocking damage. Yet, only a small portion of the injected fluid (less than 20%) could be recovered during flowback operation. Moreover, there is no good correlation between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 110 publications
0
13
0
Order By: Relevance
“…A large number of studies have also confirmed that residual fracturing fluid can promote fracture propagation through water–rock interaction during shut-in . Based on this, researchers demonstrated the feasibility of utilizing the positive effect of residual fracturing fluid to create fractures by reducing the amount of flowback fluid and believed that this was a feasible strategy for the efficient development of shale gas reservoirs . In this paper, the oxidative stimulation method is proposed.…”
Section: Introductionmentioning
confidence: 93%
“…A large number of studies have also confirmed that residual fracturing fluid can promote fracture propagation through water–rock interaction during shut-in . Based on this, researchers demonstrated the feasibility of utilizing the positive effect of residual fracturing fluid to create fractures by reducing the amount of flowback fluid and believed that this was a feasible strategy for the efficient development of shale gas reservoirs . In this paper, the oxidative stimulation method is proposed.…”
Section: Introductionmentioning
confidence: 93%
“…On the one hand, some scholars stated that low viscosity represents weak proppant carrying capacity, small induced fracture width, low flowback rate, and large reservoir damage, which is not conducive to gas production, ,, whereas some scholars also suggested that the pore pressure field and thermal stress caused by low viscosity and high diffusion coefficient of SCCO 2 jointly reduce the effective stress and induce the shear failure of natural fractures so that it is easier to enter the primary fractures of the reservoir by pressure infiltration and promote the formation of the fracture network. ,, Furthermore, today’s shale reservoir flowback rates are all low (<20%) of injecting fluids, and the low flowback corresponds to higher gas production by observation in the production process of several shale gas reservoirs. Thus, the industry is also trying to increase the “soaking time” or zero flowback rates for better production. …”
Section: Stimulation Of Shale Gas Reservoir By Scco2 Fracturingmentioning
confidence: 99%
“…The molecular-level structures and chemistries of mineral surfaces are also expected to influence the wetting characteristics and thus make the problem more complex. Furthermore, these wetting characteristics not only play a crucial role in the wetting process but also profoundly influence the processes of flow, displacement, and imbibition in porous media. , A typical example is the spontaneous imbibition process of hydraulic fracturing fluid into shale reservoirs, where the amount of water lost can be severely overestimated if the influences of precursor films and dynamic contact angle are not considered. , …”
Section: Introductionmentioning
confidence: 99%